Successful Treatment of Annular Elastolytic Giant Cell Granuloma with Tranilast and Topical Glucocorticoid under the Strict Restriction of Sun Exposure - Hidetoshi Takahashi; Katsuhiko Satoh; Akiyoshi Takagi; Akemi Ishida-Yamamoto; Hajime Iizuka (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
Annular elastolylic giant cell granuloma (AEGCG) is a rare granulomatous skin disease characterized by loss of elastic fibers accompanied with elastophagocytosis by multinucleated giant cells. The clinical appearance shows annular and serpiginous plaques with hypopigmentation or skin atrophy. Ultraviolet irradiation, heat, or other unknown factors are supposed to induce pathogenic alternation [1]. The treatment for AEGCG remains unestablished and various therapeutic modalities including intralesional and systemic glucocorticoids, psoralen plus ultraviolet A irradiation, cryotherapy,retinoids, fumaric acid esters, pimecrolimus and minocycline are applied [2,3]. We report a case of AEGCG successfully treated with oral tranilast and topical glucocorticoid with sunscreens